Patterning of Wafer‐Scale MXene Films for High‐Performance Image Sensor Arrays. Issue 17 (20th March 2022) - Li, Bo; Zhu, Qian‐Bing; Cui, Cong; Liu, Chi; Wang, Zuo‐Hua; Feng, Shun; Sun, Yun; Zhu, Hong‐Lei; Su, Xin; Zhao, Yi‐Ming; Zhang, Hong‐Wang; Yao, Jian; et al.
Abstract: As a rapidly growing family of 2D transition metal carbides and nitrides, MXenes are recognized as promising materials for the development of future electronics and optoelectronics. So far, the reported patterning methods for MXene films lack efficiency, resolution, and compatibility, resulting in limited device integration and performance. Here, a high‐performance MXene image sensor array fabricated by a wafer‐scale combination patterning method of an MXene film is reported. This method combines MXene centrifugation, spin‐coating, photolithography, and dry‐etching and is highly compatible with mainstream semiconductor processing, with a resolution up to 2 µm, which is at least 100 times higher than other large‐area patterning methods reported previously. As a result, a high‐density integrated array of 1024‐pixel Ti3 C2 T x /Si photodetectors with a detectivity of 7.73 × 10 14 Jones and a light–dark current ratio ( I light / I dark ) of 6.22 × 10 6, which is the ultrahigh value among all reported MXene‐based photodetectors, is fabricated. This patterning technique paves a way for large‐scale high‐performance MXetronics compatible with mainstream semiconductor processes. Abstract : MXenes are promising for future electronics and optoelectronics; however, previously reported patterning methods lack efficiency, resolution, and compatibility with mainstream semiconductor processing. Here, a wafer‐scale combination patterning method with a resolution up to the micrometer scale is developed, resulting in an integrated array of 1024‐pixel Ti3 C2 T x /Si photodetectors with a record‐high detectivity of 7.73 × 10 14 Jones.